An online social network for emergency management. (12th February 2010) - White, Connie; Plotnick, Linda; Kushma, Jane; Hiltz, Starr Roxanne; , Murray Turoff
Online Social Networking Sites (SNSs) are becoming extremely popular and can be employed in a variety of contexts. They permit the establishment of global relationships that are domain related or can be based on some need shared by the participants. Emergency domain-related websites, each with their own stated mission, are becoming widespread. Can a social network offer a solution to bringing emergency domain-related entities together as a 'one-stop shop'? We propose to investigate whether the social network paradigm can be used to enable individuals and organisations to collaborate in mutually beneficial ways, in all stages of emergency management: mitigation, preparedness, response and recovery. Emergency management students were surveyed to examine the concept of social networks and their acceptance as a potential tool. The results of this exploratory research show overwhelming agreement that SNSs should be considered a viable solution to the problems plaguing information dissemination and communications in the emergency domain.